2015
DOI: 10.1007/s10712-015-9322-6
|View full text |Cite
|
Sign up to set email alerts
|

The 3D Attenuation Structure of Deception Island (Antarctica)

Abstract: The seismic and volcanological structure of Deception Island (Antarctica) is an intense focus topic in Volcano Geophysics. The interpretations given by scientists on the origin, nature, and location of the structures buried under the island strongly diverge. We present a high-resolution 3D P-wave attenuation tomography model obtained by using the coda normalization method on 20,293 high-quality waveforms produced by active sources. The checkerboard and synthetic anomaly tests guarantee the reproduction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 60 publications
(114 reference statements)
5
42
0
Order By: Relevance
“…Attenuation is more sensitive to temperature gradients and melt than velocity; thus, it is better able to define these high‐melt pockets. Other studies have shown similar discrepancies in size of high‐ Qp1 and low‐ V p anomalies [e.g., Prudencio et al , ].…”
Section: Discussionsupporting
confidence: 58%
“…Attenuation is more sensitive to temperature gradients and melt than velocity; thus, it is better able to define these high‐melt pockets. Other studies have shown similar discrepancies in size of high‐ Qp1 and low‐ V p anomalies [e.g., Prudencio et al , ].…”
Section: Discussionsupporting
confidence: 58%
“…Within the frequency range 3-18 Hz, a value of 250 m is obtained for on-volcano stations and 430 m for off volcano. 250 m is comparable with typical values of between 100 m and 1000 m found at other volcanic sites [8,9,[38][39][40][41][42] where scattering effects have been observed to dominate over intrinsic attenuation. However, away from the strongly scattering regime close to a volcano, typical crustal values are in the range of 100 km and so 430 m for off-volcano stations is several orders of magnitude lower than it should be.…”
Section: Diffusionsupporting
confidence: 84%
“…A way to solve these difficulties is to jointly interpret tomography images based on the measurement of different physical quantities that greatly help in the recognition of zones with different geological characteristics. There are new examples in which velocity (traveltime) tomography is associated with seismic wave attenuation imaging [e.g., Martinez‐Arevalo et al , ; De Siena et al , ; Prudencio et al , ]. This association is essential in volcanoes, where the correct interpretation of the spatial distribution of the physical properties in terms of partial melt materials is necessary.…”
Section: Introductionmentioning
confidence: 99%